The Effect Of Leadership on Employees Perfomance in Mayors Office South Jakarta - Fini Amrani; Makruf Akbar; Muchlis R Luddin (LPPM of NAROTAMA UNIVERSITY)
The purpose of this study was to determine the effect of leadership on employee performance in the South Jakarta mayor's office. The research used was a survey with a casual design. The number of respondents was 125 employees, the sampling technique was done by simple random sampling of 265 South Jakarta mayor employees..